Hydrodynamic cavitation as a new approach for sugarcane bagasse pretreatment aiming to second generation ethanol production - Hilares, Ruly Terán (2017)
Renewable energy sources have been proposed as a viable option to mitigate the consumption and the dependence of fossil fuels. Among the available alternatives, lignocellulosic biomass has shown great potential for bioenergy generation, and biofuels as ethanol can be obtained by fermentation from sugars present in cellulosic and hemicellulosic fractions of biomass. However, for the efficient release of fermentable sugars during the enzymatic hydrolysis step, a pretreatment process is required to modify the material in its structure and composition. In this context, hydrodynamic cavitation (HC) was proposed in this work as a new and promising alternative for pretreatment of sugarcane bagasse. Firstly, the variables NaOH concentration, solid/liquid (S/L) ratio and HC process time were optimized in HC assisted pretreatment. In optimized conditions (0.48 mol/L of NaOH, 4.27% of S/L ratio and 44.48 min), high lignin removal (60.4%) and enzymatic digestibility of cellulose fraction (97.2%) were obtained. Based in those results, new variables (inlet pressure, temperature, alkali concentration) were included for evaluation in a second stage of the study aiming to reduce the HC pretreatment time. In this case, temperature and álcali concentration showed more significance on lignin removal and hydrolysis yield of carbohydrate fraction in pretreated biomass. No significant difference in pretreatment efficiency was observed in 20 and 30 min of process time in the best conditions (70 °C, 3 bar of inlet pressure and 0.3 mol/L of NaOH). The dimensionless cavitation number influence also was evaluated in two levels (0.017 and 0.048), resulting higher efficiency using low cavitation number which was obtained using orifice plate with 16 holes (1 mm of diameter). Using the last optimized conditions and lower temperature (60 °C instead 70 °C) in order to avoid the foam formation when black liquor is reused, other alkalis (Ca(OH)2, Na2CO3, KOH) were evaluated in combination with HC and compared to the use of NaOH. High enzymatic conversions of carbohydrate fraction were observed in biomass pretreated using KOH-HC and NaOH-HC; additionally, NaOH black liquor was reused in 10 sequential batches. The pretreated biomass using fresh and reused black liquor were mixed and used for simultaneous saccharification and fermentation process (SSF) in interconnected column reactors, resulting in 62.33% of hydrolysis of total carbohydrate fractions and 17.26 g/L of ethanol production (0.48 g of ethanol/g of glucose and xylose consumed). Finally, the addition of oxidant agent (H2O2) in the alkali HC-process was optimized. In selected conditions (0.29 mol/L of NaOH, 0.78 % v/v of H2O2 and 9.8 min), 95,43% and 81.34% of enzymatic hydrolysis yield of cellulose and hemicellulose fraction were achieved respectively, using 5% of solid loading (S/L) in the hydrolysis process. When packed bed flow-through column reactor using 20% of S/L was used, 74.7% cellulose hydrolysis yield was reached. Sugars present in hydrolysate were also fermented into ethanol in bubble column reactor resulting in a yield value of 0.49 g/g and 0.68 g/L.h of productivity. By analyzing the results as a whole, HC was shown as a promising technology to accelerate the pretreatment time under mild conditions, showing advantages as simplicity of system and possibility to application in industrial scale.